Modeling Satellite Gravity Gradient Data to Derive Density, Temperature, and Viscosity Structure of the Antarctic Lithosphere. Issue 11 (16th November 2019) - Pappa, F.; Ebbing, J.; Ferraccioli, F.; van der Wal, W.
Abstract: In this study we combine seismological and petrological models with satellite gravity gradient data to obtain the thermal and compositional structure of the Antarctic lithosphere. Our results indicate that Antarctica is largely in isostatic equilibrium, although notable anomalies exist. A new Antarctic Moho depth map is derived that fits the satellite gravity gradient anomaly field and is in good agreement with independent seismic estimates. It exhibits detailed crustal thickness variations also in areas of East Antarctica that are poorly explored due to sparse seismic station coverage. The thickness of the lithosphere in our model is in general agreement with seismological estimates, confirming the marked contrast between West Antarctica (<100 km) and East Antarctica (up to 260 km). Finally, we assess the implications of the temperature distribution in our model for mantle viscosities and glacial isostatic adjustment. The upper mantle temperatures we model are lower than obtained from previous seismic velocity studies. This results in higher estimated viscosities underneath West Antarctica. When combined with present‐day uplift rates from GPS, a bulk dry upper mantle rheology appears permissible. Plain Language Summary: The solid Earth structure of the Antarctic continent is still poorly explored due to the coverage of up to 4‐km‐thick ice sheets and its remote location. Robust knowledge of its characteristics is, however, essential to understand the Earth's response to ice mass changes (glacial isostatic adjustment). Of particular interest are the depth and geometry of the main subsurface boundaries, which are the interface between crustal and mantle rocks (Moho discontinuity) and the base of the rigid tectonic plate (lithosphere). Since both of them are accompanied by changes in rock density, we used gravimetric data from the Gravity Field and Steady‐State Ocean Circulation Explorer satellite to build a 3‐D model of Antarctica's deep structure. Rock composition according to temperature and pressure is taken into account. Rock composition according to temperature and pressure is taken into account and the model as a whole is internally consistent. As a result, we present a continental‐scale Moho depth map that shows novel details. From the temperature distribution in our model, we derive present‐day uplift rates of the solid Earth's surface, which are a key parameter in estimating the future ice sheet evolution. Key Points: A 3‐D model of Antarctica's lithosphere is derived from satellite gravity gradient data and self‐consistent thermodynamic modeling Moho depth values show a root‐mean‐square misfit of less than 7 km with local seismic estimates at the points where data are available Mantle viscosity in West Antarctica is 10 19 Pa·s, while the elastic lithosphere for GIA models is up to 150 km thick in East Antarctica